Total lesion glycolysis as a predictor of clinical T3–4a laryngeal cancer with laryngectomy or nonlaryngectomy. Issue 40 (8th October 2021) - Suzuki, Hidenori; Tamaki, Tsuneo; Terada, Hoshino; Nishio, Masami; Nishikawa, Daisuke; Beppu, Shintaro; Sawabe, Michi; Hanai, Nobuhiro
Abstract : Abstract: The purpose of the present study is to investigate whether the 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake parameter is related to survival outcomes for patients with clinical T3– T4a laryngeal cancer with various definitive treatments including total laryngectomy (TL). Parameters of 18 F-FDG uptake in the primary tumors of 46 cases which were assessed by positron emission tomography with computed tomography were enrolled in the present observation study. Monovariate or multivariate survival analyses were performed with log-rank test or Cox regression model, with the hazard ratio (HR) and 95% confidence interval (CI), respectively. Cutoff values of the 18 F-FDG uptake parameters were determined by the lowest P -value for monovariate overall survival. In the monovariate analysis, both metabolic tumor volume ≥13.1 and total lesion glycolysis (TLG) ≥46.5 were significantly associated with shorter overall survival, and TLG ≥46.5 was also related to a reduction in distant metastasis- free survival. In the multivariate analysis adjusting for clinical T classification (cT4/cT3) and treatment group (TL/non-TL), TLG (≥46.5/<46.5) was associated with both poorer overall (HR: 3.16, 95% CI: 1.10– 9.49) and distant metastasis- free (HR: 8.91, 95% CI: 1.93– 62.6) survival. In conclusion, TLG is a predictor for survival in laryngeal cancer.